2005
DOI: 10.1158/1055-9965.epi-05-0260
|View full text |Cite
|
Sign up to set email alerts
|

Multivitamin and Alcohol Intake and Folate Receptor α Expression in Ovarian Cancer

Abstract: Folate receptor A (FRA) expression in epithelial ovarian cancer may be related to folate intake. We examined this association using multivitamin intake, a proxy for folic acid, and assessed whether the relation was modified by alcohol intake, a folate agonist. Cases (n = 148) with suspected epithelial ovarian cancer, of ages z20 years, were seen at Mayo Clinic, Minnesota, between 2000 and 2004; those with tumor specimens (n = 108) were included in analyses. Outpatient controls (n = 148) without cancer and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
0
24
1
Order By: Relevance
“…An additional negative control was liver tissue on each TMA. Positive controls were ovarian cancer specimens (not included in this study) that had previously been identified as expressing FRα using a polyclonal antibody [15]. After washing the slides, signals were detected using the mouse MACH3 system (Biocare Medical, Walnut Creek, CA).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…An additional negative control was liver tissue on each TMA. Positive controls were ovarian cancer specimens (not included in this study) that had previously been identified as expressing FRα using a polyclonal antibody [15]. After washing the slides, signals were detected using the mouse MACH3 system (Biocare Medical, Walnut Creek, CA).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In healthy individuals, FOLR1 expression is often limited to the apical surfaces of epithelium in the lung, kidney and choroid plexus but is overexpressed in a variety of solid tumours such as ovarian cancer, non-small cell lung cancer, breast cancer, kidney cancer and high-grade osteosarcoma (2629). It is hypothesized that FOLR1 upregulation in solid malignancies is due to the increased metabolic requirements for folates to fuel nucleic acid synthesis and cellular growth (30). The biological relevance of folates, to carcinogenesis has thus made FOLR1 an attractive therapeutic target in ovarian cancer, especially those of epithelial etiology, where FOLR1 is upregulated in approximately 90% of the cases (28).…”
Section: Introductionmentioning
confidence: 99%
“…A high dietary folate intake has been reported to associate with a lower risk of developing ovarian cancers, in particular, those who consume alcohol [6], [7], [8], [9]. It is closely related to its function on DNA synthesis and its involvement in the related methionine metabolic pathway essential for DNA methylation.…”
Section: Introductionmentioning
confidence: 99%